Mulheres quilombolas e ações de afirmação territorial, Uruaçu-GO - Leao, Eleusa Maria (2019)
In Brazil, after the Federal Constitution of 1988 and by force of social movements, a complex legal pageant araise to enable the remnant populations of the quilombos to organize themselves in search of recognition and conquest of rights denied them throughout history. In this sense, numerous communities have been or are being recognized as remaining communities of quilombos. The Urban Community João Borges Vieira is part of this universe and since its formation has been developing strategies to, from the existing legal framework, conquer territory and re (build) its territorialities. The objective of the thesis is to examine the strategies of territorial affirmation and identity construction undertaken by the women of the Urban Quilombola Community João Borges Vieira, located in the city of Uruaçu-GO, created in 2008 and recognized as such by the Palmares Cultural Foundation in 2009. In community emphasize the actions of women and, in this sense, the research analyzes the performance of these individuals who long for work and income while at the same time conquering rights and territorial demarcation. Thus, the study reveals the historical process of construction of the quilombola territory, focusing on the organization of the Community João Borges Vieira, who created an Association of Remnants of Quilombo glimpsed in the production of handicrafts, by way of solidarity economy, the way to achieve ethnic, political, territorial and certain financial autonomy of families. The junction of the drumming, music and dance have become ways, aptness of the community to territorially affirm their belongings to society, assuming their identity representations. The territorial demarcation also goes through the transformation of some schools into educational institutions, with quilombola orientation. In 2019, the association presents important performance in the role of catalyzing agent of conquest for the black people of Uruaçu and region, regardless of whether they are quilombolas or not. This is a qualitative research, based on interviews and observation in the field. The research evidenced the achievements already achieved by the members and the community in terms of visibility, territorial affirmation and identity, highlighting also the ethnic / social bonds, reciprocal relations existing between the different communities of northern Goiás, providing intertwining and sharing of knowledge and actions . He also pointed out that, despite the possibilities apparently provided by existing legislation, the difficulties faced by community members in terms of the achievement of work and income and ethnic affirmation of quilombola blacks are still immense, since they lack effective public policies that ampare.